If you look for local innovations, you will find them: Exciting next steps for the Living Lab for People in Nandi County - Habermann, Birgit; Kibet, Walter (International Livestock Research Institute, 2024)
The Living Lab for People has taken significant strides towards becoming a hub for locally led adaptation innovations in Nandi County as the Nandi County government and Kaimosi Agricultural Training Centre hosted the first International Livestock Research Institute (ILRI) pilot. Living Lab for People is defined as a space for citizens to co-design innovations in real-world settings. In 2024, the Living Lab for People board issued the first call for innovation cases through social media and the extension system. The idea was to capture a broad range of ideas and then screen for the most innovative ones aligned with the aim of low emission food system development.